6-Bromo-1-[2-(2-oxo-1,3-oxazolidin-3-yl)ethyl]-1H-imidazo[4,5-b]pyri din-2(3H)-one - Bel-Ghacham, H.; Rodi, Y.K.; Saffon, N.; Essassi, E.M.; Ng, S.W. (International Union of Crystallography, 2010)
The title compound, C(11)H(11)BrN(4)O(3), features an ethane fragment substituted with an almost planar (r.m.s. deviation = 0.019 angstrom) imidazo[4,5-b]pyridone ring system and an envelope-shaped oxazolidine unit on separate C atoms. The N-CH(2)-CH(2)-N torsion angle is 52.5 (4)degrees. In the crystal, pairs of molecules are linked by N-H center dot center dot center dot O hydrogen bonds into centrosymmetric dimers.